1991
DOI: 10.1111/j.1432-1033.1991.tb16010.x
|View full text |Cite
|
Sign up to set email alerts
|

A green 2,4‐pentadienoyl‐CoA reductase from Clostridium aminovalericum

Abstract: 2,CPentadienoyl-CoA reductase from Clostridium aminovalericum was purified to homogeneity (170 -182 kDa). PAGE in the presence of SDS revealed a single band (44 kDa) indicating a homotetrameric structure. The native enzyme had a green colour and contained 0.4 mol FAD/subunit. Its unusual ultraviolet/visiblespectrum showed absorption maxima at 270,402 and 715 nm as well as shoulders at 278, 360,450 and 500 nm. Removal of the prosthetic group at pH 2 in the presence of salt and charcoal yielded a colourless and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…This transient introduction of a double bond activates the 7-hydrogen to be easily removed as a proton [32]. In vivo 2,4-pentadienoyl-CoA is released from the enzyme and reduced in a different manner by 2,4-addition of a proton and a hydride to 3-pentenoyl-CoA, which is catalysed by a different also FAD-containing greenish reductase [33]. 3-Pentenoyl-CoA is isomerized to 2-pentenoyl-CoA, which disproportionates to acetate, propionate and valerate [30] …”
Section: Dehydration Of 5-hydroxyvaleratementioning
confidence: 99%
“…This transient introduction of a double bond activates the 7-hydrogen to be easily removed as a proton [32]. In vivo 2,4-pentadienoyl-CoA is released from the enzyme and reduced in a different manner by 2,4-addition of a proton and a hydride to 3-pentenoyl-CoA, which is catalysed by a different also FAD-containing greenish reductase [33]. 3-Pentenoyl-CoA is isomerized to 2-pentenoyl-CoA, which disproportionates to acetate, propionate and valerate [30] …”
Section: Dehydration Of 5-hydroxyvaleratementioning
confidence: 99%
“…The precipitate was discarded and the remaining solution applied to a phenylsepharose HP column. For continuous routine measurements 3-pentenoyl-CoA served as substrate and Meldola blue (8-dimethylamino-2,3-benzophenoxazine) together with INT [2-(4-iodophenyl)-3-(4-nitrophenyl)-5-phenyltetrazolium chloride] was used as electron acceptor (kcat = 16s -1) (Eikmanns & Buckel, 1991c). The most active colored fractions were pooled and purified further by size-exclusion chromatography on Superdex 200 followed by anion-exchange chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…Incubation of the enzyme with an excess of FAD results in 0.9mol FAD/subunit and the specific activity increases twofold. The unusual UV-visible spectrum of this greenish enzyme (absorption maxima at 404 and 707 nm, shoulder at 371 and 460nm) can be converted to that of a normal yellow flavoprotein (absorbance maxima at 370 and 450nm) by removal of the prosthetic group followed by reconstitution with FAD, but not by reduction with dithionite followed by reoxidation by air (Eikmanns & Buckel, 1991c). Neither of these treatments abolished enzymic activity, indicating that the green charge-transfer complex was not an intermediate in the reaction pathway.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The UV-visible spectrum of DCO indeed provided initial evidence that the enzyme is a flavo/FeS protein, and it was shown that 1,5-dienoyl-CoA reduced these cofactors. DCO, old yellow enzymes, and 2,4-dienoyl-CoA reductases use ␣,␤-unsaturated carbonyl compounds as electron donors (30,(32)(33)(34)(35)(36)(37). Whereas the latter two reduce their substrates most often with NADPH, only DCO catalyzes an irreversible oxidation of its substrate.…”
Section: Properties Of Dco and Comparison With Other Enzymes-mentioning
confidence: 99%